Identifying factors in estimation of Body Mass Index : cohesion between environmental factors and physical activity - Md. Nofayer Haque; Muhammad Mahady Hasan; Azizur Rahman (International Journal of Public Health Science (IJPHS), 2019)
Body Mass Index (BMI) is a good indicator of nutritional status in a population. It can be considered as an indicator of overall health condition. Beside Genetic aspects the BMI level is affected by different factors, such as socio economic, environmental and physical activity level. This study investigated about the effects of different physical and environmental factors on the BMI level of a sample of 75 adults and fit a suitable ANN based model. The mean BMI was 23.8671±2.89217 kg/m2. The Pearson correlation, independent sample T-test, one-way ANOVA, ANN, regression analysis was used to extract the variables which significantly influenced the BMI. The statistical analysis showed that, despite the apparent association of BMI with physical activity level, it is influenced by several factors such as age, distance to bus stop, dieting, daily exercise, marital status, educational level and recreational facilities. It shows that daily exercise, recreational facility, education level has significant impact in estimation of Body Mass Index (BMI).